Kepadatan dan Pola Distribusi Kima (Tridacnidae) di Perairan Pulau Lemukutan Kalimantan Barat - Ikhsan, Arman Nur; Panggabean, Grin Tommy; Alkadrie, Syarif Iwan Taruna; Saputra, Andrian; Hidayat, Enjang Hernandi; Firdaus, Moh Rezha Sabda; Djuniadi, Sj.; Saniswan, Yuda; Putra, Eko Rahmanza (Dept. Marine Science, 2026)
Lemukutan Island is a marine conservation area in Bengkayang Regency, West Kalimantan, with high marine resource potential. Besides supporting tourism activities such as diving and snorkeling, its waters host ecologically important giant clams (Tridacnidae), which function as natural biofilters in reef ecosystems. However, information regarding the biodiversity and population status of giant clams in this area remains limited. This study aimed to assess the density and distribution patterns of giant clams in the waters of Lemukutan Island. Field data were collected in July 2025 at four observation stations representing the eastern and western parts of the island using the belt transect method (50m x 5 m). Data analysis included calculations of density, relative abundance, and distribution patterns using the Morisita Index. A total of 329 individuals belonging to three species were recorded: Tridacna crocea, T. maxima, and T. squamosa. T. crocea was the most dominant species at all stations, with the highest average density (0.231 ind/m²) and relative abundance (14.732%). In contrast, T. squamosa showed the lowest average density (0.067 ind/m²). Station 2 exhibited the highest overall density (0.254 ind/m²) and relative abundance (16.241%) compared to other stations. The distribution pattern of giant clams was predominantly clumped. However, a more uniform distribution of T. crocea and T. maxima was observed at Stations 3 and 4. Variations in density and distribution were closely associated with coral reef availability and water quality conditions. These findings provide baseline data to support sustainable conservation and management of giant clams in Lemukutan Island waters.